Republic of Armenia : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2006)
The staff report for the Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility focuses on the Republic of Armenia's economic environment and policy discussion. Financial sector reforms will focus on improving corporate governance, strengthening regulation and supervision, and deepening financial intermediation. Price developments should be monitored closely and monetary policy tightened further should inflation pressures increase. The authorities' plan to subsidize the local gas supplier to limit gas tariff increases for end-users is cause for concern.